Now it's your turn: read with ladybird: level 2 improve reading - Birkinshaw, Marie; Horsley, Lorraine Jackson, Shirley (Ladybird Loughborough, 1997)
This reader for 5 to 6 year olds comprises 4 stories which cover a comprehensive selection of material to help build the foundation of successful reading